2013
DOI: 10.1021/cm402225z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Application of Ultrasmall Nanoparticles

Abstract: Nanomaterials in the size range of 3–50 nm have received increased attention in the last few decades because they exhibit physical properties that are intermediate to those of individual molecules and bulk materials. Similarly, ultrasmall nanoparticles (USNPs), with sizes in the 1–3 nm range, exhibit unique properties distinct from those of free molecules and larger-sized nanoparticles. These properties are greatly sensitive to both the composition and size of the particles, and thus, the ability to control th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
280
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(281 citation statements)
references
References 175 publications
0
280
0
1
Order By: Relevance
“…Strikingly, the addition of NaCl to the solvent is associated with a small red shift of the PL emission maximum of the A-AgPVP clusters. Moreover, the addition of a reducing agent such as NaBH 4 or of an oxidizing agent like H 2 O 2 to the A-AgPVP cluster colloid was not observed to alter the spectral features of their PL emission and UV/Vis absorption spectra. These experimental results prove both the high stability of the Ag clusters and the absence of any Ag + ions in the solution.…”
Section: 5152mentioning
confidence: 93%
“…Strikingly, the addition of NaCl to the solvent is associated with a small red shift of the PL emission maximum of the A-AgPVP clusters. Moreover, the addition of a reducing agent such as NaBH 4 or of an oxidizing agent like H 2 O 2 to the A-AgPVP cluster colloid was not observed to alter the spectral features of their PL emission and UV/Vis absorption spectra. These experimental results prove both the high stability of the Ag clusters and the absence of any Ag + ions in the solution.…”
Section: 5152mentioning
confidence: 93%
“…Almost all previous studies have exclusively used trialkylphosphine chalcogenides (R3P=E; E= S, Se, Te) for the production of metal chalocogenide QDs, and from spectroscopic analysis it was proposed that "magic-sized" nanocrystals (MSNs) (<1.5 nm in diameter) are formed as key intermediates, which undergo further growth to form QDs. [15][16][17][18] Because of high reaction temperature, the appearance and disappearance of these intermediate nanocrystals were very rapid. Thus they have not been isolated and characterized, and even their structural properties remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Colloidal approaches, which enable governing the thermodynamics and kinetics of nucleation, growth, and crystallization of solids in liquid media Kwon and Hyeon, 2008;Erdemir et al, 2009;Wang et al, 2015), have demonstrated to be powerful synthetic routes to precisely phase-engineered NCs for a huge materials library across diverse size-morphological regimes Jun et al, 2006;Park et al, 2007;Cozzoli, 2008;Baghbanzadeh et al, 2011;Kim et al, 2013;Yang et al, 2013;Lhuillier et al, 2015). Recently, to meet the raising demand for intelligent nanosystems capable to exhibit enhanced, diversified, or even completely unprecedented properties and capabilities for multitask applications, synthetic nanochemistry research has opened up new horizons in the design, creation, and mastering of increasingly complex NC-based assemblies and architectures.…”
Section: Introductionmentioning
confidence: 99%